Brush like polyaniline on vanadium oxide decorated reduced graphene oxide: Efficient electrode materials for supercapacitor. (April 2019) - Yasoda, K. Yamini; Mikhaylov, Alexey A.; Medvedev, Alexander G.; Kumar, M. Sathish; Lev, Ovadia; Prikhodchenko, Petr V.; Batabyal, Sudip K.
Graphical abstract: Polyaniline nanofibres were fabricated on the V3 O7 coated reduced graphene oxide for supercapacitor electrode. Highlights: V3 O7 nanoparticles decorated rGO nanosheets were fabricated by thermal explosive method. Brush like 1D structures were developed on polymerisation of aniline on V3 O7 -rGO composites. The HCl doped PANi composites (V3 O7 -rGO-PANi) exhibits excellent electrochemical properties. 579 F/g specific capacitance were recorded at 0.2 A/g which also showed a good stability of 94% over 2500 cycles. Abstract: Vanadium oxides (V3 O7 ) have been used as electrode materials for supercapacitor applications because of its multiple oxidation states. V3 O7 nanoparticles were coated on reduced graphene oxide (rGO) from a peroxovanadate-rGO composite by thermal microexplosive decomposition method. These V3 O7 decorated rGO were made composite with the flexible multi redox conducting polymer (Polyaniline). The performance of the composite materials as electrode for supercapacitors was analyzed in a 3-electrode cell, obtaining a specific capacitance of about 579 F g −1 at 0.2 A g −1 specific current. Cycling stability is one of the main barriers noticed in V3 O7, which limits the practical performance of supercapacitors. This is overcome by modifying V3 O7 with rGO and polyaniline composites which produces good electrical contact resulting in higher capacitances and enhanced cycling stability when compared to pristine V3 O7 . A superior electrochemical performance and ultra-long cyclic stability of 94% over 2500 cycles was obtained through these developed electrodes.